2022
DOI: 10.1177/2156759x221106806
|View full text |Cite
|
Sign up to set email alerts
|

Tiered Supports for the Class of 2021 in Unprecedented Times: A High School Counseling Department’s Journey

Abstract: The impact of COVID-19 and the racial awakening of the United States intensified the inequities already present in many K–12 schools. Authors report a practitioner-focused case study of a high school counseling department integrating multitiered systems of support (MTSS) into their comprehensive school counseling program during the 2020–2021 school year, in response to both a global pandemic and the racial justice movement. Authors describe school counselors’ passionate commitment to supporting the school and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A potential explanation for this result is that school counselors extracted meaning, a dimension of psychological empowerment, from an otherwise negative experience such as COVID-19 which seems to be supported by the extant school counseling and broader literature (Narayanan & Ordynans, 2022;Yang et al, 2021). For example, during the pandemic, school counselors were required to demonstrate resiliency and dedication to their students and school community which may have elicited further passion for their work engagement (Tillery et al, 2022). In another study, Yang et al (2021) longitudinally examined the extent to which meaning-making of negative experiences helped people cope, 3 months before, during, and after the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential explanation for this result is that school counselors extracted meaning, a dimension of psychological empowerment, from an otherwise negative experience such as COVID-19 which seems to be supported by the extant school counseling and broader literature (Narayanan & Ordynans, 2022;Yang et al, 2021). For example, during the pandemic, school counselors were required to demonstrate resiliency and dedication to their students and school community which may have elicited further passion for their work engagement (Tillery et al, 2022). In another study, Yang et al (2021) longitudinally examined the extent to which meaning-making of negative experiences helped people cope, 3 months before, during, and after the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, our results indicated that participants in the pre‐COVID‐19 condition had higher scores on multicultural competence compared with their counterparts in the current COVID‐19 condition. School counselors in the current COVID‐19 condition may have scored lower in multicultural competence than those in the pre‐COVID‐19 condition because the pandemic further exacerbated the lived experiences and challenges of low‐income families and students of Color (Huck & Zhang, 2021; Kruczek et al., 2022; Tillery et al., 2022). For example, Kruczek and colleagues (2022) found that school counselors’ reported challenges during the pandemic included effectively meeting the needs of historically marginalized students and students with special needs, as well as the limited help‐seeking behavior from the most vulnerable families.…”
Section: Discussionmentioning
confidence: 99%